EFL STUDENTS’ PERCEPTION TOWARD ONLINE LEARNING DURING COVID 19 - Dewi Yana; Aulia Putri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
During the Covid 19 Pandemic, lectures were carried out totally via online learning. This study aims at describing the EFL students’ perception on the issue. This study applied a descriptive method and involved 102 students of the English Education Study Program- Riau Kepulauan University. The questionnaire was in 5 Likert scale and open questions which was modified from three components of Information Technology Innovation-instrument by Moore and Benbasat namely relative advantage, ease of use, and compatibility. It also was settled up to get information on challenge, obstacles, and students’ negative opinion toward the online-learning. The data was taken at the end of even semester (July) on academic year 2019/2020, and it was distributed by sending online survey to the year 1 to 4 of English Education Study Program of UNRIKA. In analyzing the data, it was computed to get the frequencies and percentages. The results are displayed in the form of chart and tables, and it is found that students’ perception can be considered as the important factor in applying the online learning particularly in the Covid 19 pandemic era.